VD_FINDINFO Arrêt / 2018 / 862 vom 22. Oktober 2018 - VD Tribunal cantonal (2018)
INDEMNITÉ DE CHÔMAGE, EMPLOYEUR, POSITION ANALOGUE, RÉSILIATION | 31 al. 1 LACI, 31 al. 3 LACI, 31 al. 3 let. c LACI, 8 al. 1 LACI